Deconstructing ABS-CBN and CCP's Kulturang Handog sa Bayan - Sanchez, Katherine C.
This study focused on how classical art and popular art were valued in the TV special Kulturang Handong sa Bayan. Kultura's different aspects of production design, performance interpretation, performers and language in the dances, the songs, and in the spiels were analyzed using discourse analysis as framework. Interviews with the show's producers and artists were also analyzed with the same framework. The study showed the Kultura promoted classical art as valuable, and as such, should be brought to the masses for them to appreciate. In doing this, the value of popular art was neglected or was given less priority. Discourse analysis is about finding contradictions and omissions and not just relying on the dominant and obvious themes of text. In doing so, text such as Kultura are opened up to the possibility of changing it from a site where some discourses either dominate of subjugate subjects into a site where hegemonoc practices can be resisted.